Land Rights: Validity of Ownership and Tenure - Piyalelo, Phra Thanoo (Journal of Graduate MCU KhonKaen Campus, 2022)
This academic article aim to present content about land rights Ownership and possession for proper use Land is a valuable real estate. People have a desire to own and own land and the demand is increasing day by day, especially in areas where progress or utilities reach. whether for use as a residence industrial farming, or for commercial purposes, however, all people with land rights deserve a thorough study laws, in having the right to have ownership of the land, no problems later on